1981
DOI: 10.1007/bf02906201
|View full text |Cite
|
Sign up to set email alerts
|

A fluorimetric method for measuring 1,3∶1,4-β-glucan in beer, wort, malt and barley by use of Calcofluor

Abstract: A convenient method for determining mixed linked 1,3:l,4-~-glucans in beer, wort, malt and barley is described. The fluorochrome Calcofluor, specific for ~-glucosidic linkages, is used to stain these materials. The fluorescence intensity of the final suspension is measured and the result compared with traditional ~-glucan measurements.The correlation between fluorescence intensity and (NH4)2SO4 precipitation was very good for beer and wort. The correlation between the fluorescence method and an enzymatic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 9 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The intense whitish-blue fluorescence induced on complexing of (l~3,1~4)-~-glucans with Calcofluor, a stilbene derivative and the red fluorescence induced by Congo Red, a biphenyl amino naphthylamine sulphonate derivative, has been exploited (Wood et al, 1983) in the histochemical characterization of cereal grains and cereal foods (Fulcher et aL, 1989) and a quantitative method for (l~3,1~4)-J3-glucans in solution, e.g. in beer, based on Calcofluor-complexing has been proposed (Aastrup and Jorgensen, 1988;Jensen and Aastrup, 1981;Switala et aL, 1989). A quantitative method based on specific hydrolysis by purified preparations of (l~3,1-~4)-13-glucan hydrolases (EC 3.2.1.73) (Anderson et aL, 1978;Henry and Blakeney, 1986;McLeary and Codd, 1991) is now in frequent use and the same enzyme, complexed with fluorescein isothiocyanate (FITC) or rhodamine isothiocyanate (RITC), has been used as a histochemical probe for the specific location of (1-->3,1 ~4)-13-glucan in walls of developing wheat grain (Joyner, 1985;Stone, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The intense whitish-blue fluorescence induced on complexing of (l~3,1~4)-~-glucans with Calcofluor, a stilbene derivative and the red fluorescence induced by Congo Red, a biphenyl amino naphthylamine sulphonate derivative, has been exploited (Wood et al, 1983) in the histochemical characterization of cereal grains and cereal foods (Fulcher et aL, 1989) and a quantitative method for (l~3,1~4)-J3-glucans in solution, e.g. in beer, based on Calcofluor-complexing has been proposed (Aastrup and Jorgensen, 1988;Jensen and Aastrup, 1981;Switala et aL, 1989). A quantitative method based on specific hydrolysis by purified preparations of (l~3,1-~4)-13-glucan hydrolases (EC 3.2.1.73) (Anderson et aL, 1978;Henry and Blakeney, 1986;McLeary and Codd, 1991) is now in frequent use and the same enzyme, complexed with fluorescein isothiocyanate (FITC) or rhodamine isothiocyanate (RITC), has been used as a histochemical probe for the specific location of (1-->3,1 ~4)-13-glucan in walls of developing wheat grain (Joyner, 1985;Stone, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Air bubbles interfering with the fluorescence measurements could be eliminated by treatment in a vacuum chamber or in an ultrasonic bath. It was found that for beer and wort, the 75% glycerol solution could be exchanged for a 0.5 M-glycine buffer, pH = 10.0, obtaining a true solution of the Calcofluor-13-glucan complex completely eliminating the heterogeneity problems (10). Phosphate and Carbonate buffers at pH = 10.0 were also tested, but fading of the Calcofluor-13-glucan fluorescence was here much more pronounced than in the glycine buffer.…”
Section: Solubilization Of the Precipitated Calcofluor-~-glucan Complexmentioning
confidence: 99%
“…Therefore, viscosity measurement of wort and beer is the only practical alternative, giving only an indication of l]-glucan content. Recently, a spectrofluorometric method has been described by JENSEN and AASTRUP (10), based on the ability of the fluorochrome Calcofluor specifically to bind 13-glucan (15,16,17). This preliminar method has been used to measure the content of l]-glucan in barley, malt, wort and beer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The I]-glucans in wort and beer can be measured by the AMS-method or as previously described by the use of Calcofluor (CEP-method, 15,16). The relationship between the values determined by these methods and the viscosity of wort and beer has been investigated (14,16,19), and it was shown that the 15-glucan content could not fully explain the variation in viscosity.…”
Section: Introductionmentioning
confidence: 99%